(untitled) (Journal of Accessibility and Design for All, 2019)
The goal of this research is the identification and analysis of doctoral dissertations registered in Spain that address universal accessibility as a topic in order to detect trends, scope for development and leading institutions. The TESEO database has been used as a basic tool. A significant number of dissertations on universal accessibility published in Spain between 1998-1999 and 2017-2018 academic years have been identified, although these make up a small proportion of the total number of those registered. Specifically, the database contains 108 dissertations on this subject. The most common topics are accessibility to digital services in general, accessibility to art, culture and tourism, inclusive education, assistive products, accessibility to the urban environment, transport and buildings, and accessibility as a fundamental right. Some of the dissertations found deal with subjects rarely studied from the point of view of universal accessibility, such as banking, communication, employment, the home and R&D&I processes. The educational institutions which have published the largest number of these dissertations on universal accessibility are the Technical University of Madrid and the University of Granada, followed by the University of Valencia and the Technical University of Valencia.